PENGUATAN KELOMPOK MASYARAKAT DALAM PENGOLAHAN PEMBERIAN MAKANAN TAMBAHAN LOKAL UNTUK PENCEGAHAN STUNTING DI NAGARI SITUJUAH LADANG LAWEH, LIMA PULUH KOTA - Helmizar Helmizar; Restu Sakinah; Queenta Gociardi; Ghina Sukma Fadhilah; Shakila Angelica Putri; Alifia Putri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Stunting is a global health issue affecting children’s growth and development, particularly in areas with limited access to adequate nutrition. This community service program aims to strengthen community groups in Nagari Situjuah Ladang Laweh in processing and utilizing local supplementary feeding (PMT) to prevent stunting related to the local PMT program currently being implemented by the government. The activity method used is training and mentoring in processing PMT based on local resources carried out by students of the Community Service Program (KKN) of Andalas University (Unand) in 2024 with a focus on community empowerment. The activity stages include identifying local food potential, technical training in PMT processing, and establishing working groups for distribution and monitoring of PMT consumption. This program also includes education on the importance of nutrition for children and monitoring child development to evaluate the effectiveness of PMT in reducing the risk of stunting. The results of the activity show an increase in the capacity of community groups in optimally utilizing local food ingredients, increased knowledge about nutrition and stunting, and changes in healthier food consumption patterns. The conclusion that can be drawn from this community service activity is an increase in community knowledge and skills, especially regarding the processing of local food as PMT. With a local approach, this program is expected to make a significant contribution to stunting prevention in the area.